Developing and Validating a UPLC‐MS Method with a StageTip‐Based Extraction for the Biogenic Amines Analysis in Fish. Issue 5 (16th April 2019) - Zhang, Jingbo; Hu, Jing; Wang, Shuai; Lin, Xinping; Liang, Huipeng; Li, Shengjie; Yu, Chenxu; Dong, Xiuping; Ji, Chaofan
Abstract: To effectively extract biogenic amines (BAs) from complex food matrices is an important issue. In this study, a stop‐and‐go‐extraction tip (StageTip)‐based method for simultaneous enrichment of six BAs including histamine, tyramine, putrescine, cadaverine, tryptamine, and β‐phenylethylamine in fish samples was developed and optimized. This StageTip‐based BAs extraction method required short extraction time, small sample size, and minimal consumption of organic solvents. In addition, an ultrahigh‐performance liquid chromatography coupled with triple quadrupole mass spectrometer was used to identify and quantify BAs without derivatization. Target recovery efficiencies of BAs from spiked fish samples ranged from 84% to 110%. Linear regression models were established to determine BAs in the range of 0.4 to 3.0 mg/L ( R 2 > 0.995). Good repeatability was obtained with relative standard deviation of peak areas (1.17 to 5.61%) and retention time (0.09 to 0.20%). High sensitivity was achieved for the detection of six BAs (0.064 to 1.00 ng/L for the limit of detection, 0.10 to 5 ng/L for the limit of quantification). The proposed method had an obvious advantage in the analysis of BAs in complex food matrices such as fish tissues since it could reflect the subtle distribution of BAs from one fish fillet. Practical Application: A StageTip‐based BAs enrichment combined with UPLC‐MS analysis method was developed and optimized, which waslow ‐cost, environmentally friendly, and with good analytical performances. As such, it has the potential to become a powerful tool for the analysis of BAs in different complex food matrices.